Nitric oxide as a mediator of gastrointestinal mucosal injury?—Say it ain't so - Paul Kubes; John L. Wallace (Mediators of Inflammation)
Nitric oxide has been suggested as a contributor to tissue injury in various experimental models of gastrointestinal inflammation. However, there is overwhelming evidence that nitric oxide is one of the most important mediators of mucosal defence, influencing such factors as mucus secretion, mucosal blood flow, ulcer repair and the activity of a variety of mucosal immunocytes. Nitric oxide has the capacity to down-regulate inflammatory responses in the gastrointestinal tract, to scavenge various free radical species and to protect the mucosa from injury induced by topical irritants. Moreover, questions can be raised regarding the evidence purported to support a role for nitric oxide in producing tissue injury. In this review, we provide an overview of the evidence supporting a role for nitric oxide in protecting the gastrointestinal tract from injury.